2013
DOI: 10.1021/cs300684y
|View full text |Cite
|
Sign up to set email alerts
|

Stability of Pt/γ-Al2O3 Catalysts in Lignin and Lignin Model Compound Solutions under Liquid Phase Reforming Reaction Conditions

Abstract: The stability of a 1 wt % Pt/γ-Al 2 O 3 catalyst was tested in an ethanol/water mixture at 225°C and autogenic pressure, conditions at which it is possible to dissolve and depolymerize various kinds of lignin, and structural changes to the catalysts were studied by means of X-ray diffraction (XRD), 27 Al MAS NMR, N 2 physisorption, transmission electron microscopy (TEM), H 2 chemisorption, elemental analysis, thermogravimetric analysis-mass spectrometry (TGA-MS), and IR. In the absence of reactants the alumina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
85
0
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 86 publications
(89 citation statements)
references
References 29 publications
2
85
0
2
Order By: Relevance
“…Ni-MoS2/ZrO2 was chosen as catalyst, as promotion by nickel previously has been shown to be slightly superior to cobalt promotion for HDO purposes [9,25] and ZrO2 was previously found as a suitable support for HDO [31][32][33][34][35] and does apparently not suffer from the instability in high concentration of water, as reported for the conventionally used -Al2O3 support for hydrotreating catalysts [9,36,37].…”
Section: Introductionmentioning
confidence: 99%
“…Ni-MoS2/ZrO2 was chosen as catalyst, as promotion by nickel previously has been shown to be slightly superior to cobalt promotion for HDO purposes [9,25] and ZrO2 was previously found as a suitable support for HDO [31][32][33][34][35] and does apparently not suffer from the instability in high concentration of water, as reported for the conventionally used -Al2O3 support for hydrotreating catalysts [9,36,37].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, studies have shown some difficulty in controlling Pt dispersion on a shows the typical resonances at 8 ppm and 65 ppm, attributed to octahedrally and tetrahedrally coordinated aluminum species, respectively [23]. Expectedly, surface overcoating followed by precursor decomposition did not lead to obvious differences in the 27 Al MAS NMR spectrum. No peaks corresponding to pentahedrally coordinated aluminum species were observed, indicating that silica deposition leads to a surface modification only, rather than the formation of any detectable (bulk) silica-alumina phases [42].…”
Section: Catalyst Characterizationmentioning
confidence: 87%
“…Solid-state 27 Al magic angle spinning (MAS) nuclear magnetic resonance (NMR) spectra were taken using a Bruker AV3 400 solid spectrometer. A high MAS rate of 12 kHz and a high magnetic field of 9.4 T helped to ensure that the spectra were quantitatively reliable.…”
Section: Characterizationmentioning
confidence: 99%
See 2 more Smart Citations